Studi Eksperimen Penggunaan Simulasi PhET dan Metode Drill dalam Pembelajaran Fisika Gerak Peluru pada Mahasiswa Teknologi Hasil Pertanian - Jules Nurhatmi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
This study aims to compare the effectiveness of using PhET simulations and the drill method in physics education, specifically on the projectile motion concept, for students of the Agricultural Technology program. The study employed a quasi-experimental method with a pretest-posttest design on two groups of students. The experimental group (R001), consisting of 37 students, used PhET simulations, while the control group (R002), consisting of 40 students, used the drill method. The results showed a significant increase in learning outcomes for both groups. The average posttest score of the PhET simulation group increased from 50.41 to 87.15, while the drill group's average score increased from 49.75 to 76.05. An independent t-test showed a significant difference between the two groups' posttest results (p<0.001). This study concludes that PhET simulations are more effective in improving students' understanding of projectile motion concepts compared to the drill method. PhET simulations allow students to manipulate variables interactively, while the drill method focuses more on repetition of problem-solving